الأثر الدلالي اللغوي للوقف في القرآن الكريم /The semantic effects of pause in the Holy Quran - Zakaria, Abd Wahab; Mustapha, Maziah (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2020)
مُلخَّص البحث تناولت هذه الدراسة الأثر الدلالي اللغوي للوقف في القرآن الكريم، هادفة إلى بيان دور العلماء القدامى من القراء واللغويين، الذين عنوا عنايات خاصة بمعرفة الوقف القرآني؛ إذْ يعدونه موضوعاً مهمًا جداً، كما قيل إنه حلية التلاوة، وزينة القارئ وبلاغ التّالي، وفهم للمستمع، وبه يعرف الفرق بين المعنيين المختلفتين والقضيتين المتباينتين والحكمين المتغايرين. وهذه الدراسة اتبعت المنهج الوصفي التحليلي، وتضمنت تعريف الوقف لغةً واصطلاحًا، وعلاقة الوقف بالقراءات القرآنية، والأثر الدلالي اللغوي للوقف في القرآن الكريم، ثم تأتي الخلاصة وفيها أهم ما توصل إليه الباحثان. استنتجت الدراسة أنّه لا بد للوقف أنْ يتفق مع وجوه التفسير الصحيحة، واستقامة المعنى وصحة اللغة، وما تقتضيه علومها، وأنّ القراءات القرآنية تختلف من واحدة إلى أخرى؛ ولذلك فلا بُدَّ من اختلاف مواطن الوقف. ويكون ذلك ضروريًّا للقارئ؛ حيث إنّ تطبيق الوقف يكون تابعًا للقراءة المتلوة؛ إذْ لاختلاف القراءات أثر في الوقوف من ناحية الدلالة، ومغزى هذا المقال الإجابة عن تساؤلات ذات علاقة بالوقف القرآني وأثره في الدلالة اللغوية والمعاني المفهومة من القراءة. الكلمات المفتاحية: الأثر الدلالي، اللغة، الوقف، القرآن الكريم، القرّاء، القراءات. Abstract The study discusses the effects of pause on the linguistic meaning in the Holy Quran through explaining the roles of early linguists and Qura’nic experts on the Qur’anic punctuation (pause). It is an important feature in beautifying the recitation, an ornamentation of the reciter that helps the understanding of the listener. Different meanings, issues and rulings are decided with it. Given the fact that Quranic recitation varies from one another, the places to pause while reciting also differ accordingly. It should, therefore, be in conformity with the type of recitation one intends to recite at a time to maintain the semantic accuracy of the Qur’an. This research intends to analyze the semantic implications of the Qur’anic pause with reference to the seven recitation methods by the early Islamic scholars. The outcome of the research would assist Qur’anic reciters to be aware of the semantic implication of pauses to avoid misrepresenting the meaning of the Quran during recitation. Keywords: Semantic effect, Language, Pause, The Holy Quran, Readers, Readings. Abstrak Kajian ini membincangkan kesan berhenti(waqaf) pada makna linguistik dalam Al-Quran dengan menerangkan peranan sarjana bahasa tradisional dan sarjana Al-Quran mengenai tanda baca waqaf yang merupakan ciri penting dalam memperelok bacaan dan dapat menjelaskan lagi pemahaman pendengar. Makna, topik dan hukum yang berbeza diputuskan dengannya. Memandangkan bacaan Al-Quran berbeza antara satu sama lain, tempat berhenti sementara membaca juga berbeza. Oleh itu, ia harus sesuai dengan jenis bacaan yang ingin seseorang baca dalam satu waktu untuk menjaga ketepatan semantik al-Quran. Penyelidikan ini bertujuan untuk menganalisis implikasi semantik waqaf al-Quran dengan merujuk kepada tujuh kaedah pembacaan oleh para sarjana Islam terdahulu. Hasil kajian ini akan membantu para pembaca Al-Quran untuk mengetahui implikasi semantik waqaf untuk mengelakkan terjadi pengertian Al-Quran yang salah kerana membaca. Kata kunci: Kesan makna, bahasa, Waqaf, Al-Quran, Pembaca, Bacaan.